2020
DOI: 10.1038/s41587-020-0656-3
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of T cell receptor repertoire profiling methods reveals large systematic biases

Abstract: Accurate profiling of T-cell receptor (TCR) repertoires is key to monitoring adaptive immunity.We systematically compared TCR sequences obtained with 9 methods applied to aliquots of the same T-cell sample. We observed marked differences in accuracy and intra-and intermethod reproducibility for alpha (TRA) and beta (TRB) TCR chains. Most methods showed lower ability to capture TRA than TRB diversity. Low RNA input generated non-representative repertoires. Results from 5'RACE-PCR methods were consistent among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
113
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 68 publications
4
113
0
Order By: Relevance
“…Only single-cell sequencing can provide paired chains. Also, the accuracy of the technology that heavily relies on PCR amplification and its capacity to detect rare clonotypes might affect results (24). Despite all these limitations, TCR sequencing carries enormous potential in particular in combination with cytometric techniques discussed above.…”
Section: Tcr Repertoire Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Only single-cell sequencing can provide paired chains. Also, the accuracy of the technology that heavily relies on PCR amplification and its capacity to detect rare clonotypes might affect results (24). Despite all these limitations, TCR sequencing carries enormous potential in particular in combination with cytometric techniques discussed above.…”
Section: Tcr Repertoire Analysismentioning
confidence: 99%
“…• To sequence the bulk repertoire of at least 10 5 purified/ enriched T cell populations, at least always separating Treg from Teffs, and using a robust method (24). • To refrain from performing single-cell TCR sequencing from peripheral blood except if relevant subsets can be enriched, i.e., by antigen-specific cytometry assays as described above.…”
Section: Tcr Repertoire Analysismentioning
confidence: 99%
“…Compared to other methods the resolution of information is much higher using less input of biomaterial. However, several comparative studies have shown that the different approaches lead to significantly different results, even when using the same input material ( 27 , 30 ). These studies indicate that there is still a need to standardize the analysis of TCR repertoires for clinical application.…”
Section: Introduction: T Cell Immunitymentioning
confidence: 99%
“…However, while the length of the CDR3 distribution is one parameter of T-cell diversity, most of the variability lies in the CDR3 sequence that is encoded within the V(D)J region, represented by b sequences, which comes in contact with an antigenic peptide (21,22). Further, previous studies leveraged mRNA-based complimentary DNA sequencing which is biased due to different mRNA content per cell and is affected by RNA input (23). Therefore, deep sequencing of the genomic CDR3 beta-region would allow a more accurate representation of the TCR diversity (23).…”
Section: Introductionmentioning
confidence: 99%
“…Further, previous studies leveraged mRNA-based complimentary DNA sequencing which is biased due to different mRNA content per cell and is affected by RNA input (23). Therefore, deep sequencing of the genomic CDR3 beta-region would allow a more accurate representation of the TCR diversity (23).…”
Section: Introductionmentioning
confidence: 99%